Stepping Stones: A Course for Basic Writers - Eisenberg, Nora and Wiener, Harvey S. (New York Random House, Inc., 1985)
Stepping Stones: A Course in Basic Writing teaches students composition skills by proceeding through the strategy most English teachers acknowledge as best for beginners: a carefully-paced inductive approach to the principles of our language. Our title reflects not only a progression of incremental learning but also an effort to lay foundations for independent thought and action in writing. By asking students to observe, to extract and to generalize, and then to practice, we feel that we have developed a sound pedagogical approach for beginning writers in college.
Keywords: Writing